Diagnostic Advancement Versus Traditional diagnosis of Kidney Diseases in Unani Medicine: Novel Biomarkers and Future Prospects - Khatoon, Tayyaba; Fahad, Ataullah; Ahmad, Naved; Gupta, Veena (International Journal of Human and Health Sciences (IJHHS), 2025)
Kidney health is critical for waste excretion, acid-base regulation, and hormone production. Lifestyle changes, including poor diet and inactivity, have increased risks kidney diseases. The study on Global Burden of Disease highlights the significant rise in death due to kidney failure, with approximately 1.2 million annual fatalities and millions more are suffering from kidney disease (KD) or acute kidney injury. KD is now a leading cause of death worldwide, particularly in India. The 2024 World Kidney Day emphasizes equitable access to kidney care. In Unani medicine, kidney diseases have long been recognized, with detailed descriptions of their functions and pathophysiology. Assessment methods for kidney function include glomerular filtration rate (GFR) estimation and proteinuria detection. Novel biomarkers such as cystatin-C, NGAL, KIM-1, and SDMA offer enhanced early detection and monitoring of kidney disease. Despite advancements, challenges in early diagnosis remain. Integrating these biomarkers into clinical practice holds the promise of better patient outcomes by enhancing diagnosis and enabling precision medicine. Continued research and standardized protocols are essential for maximizing their diagnostic potential. International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 86-92